House of Hancock: business in Boston 1724-1775 - Baxter, William Threipland (The University of Edinburgh, 1946)
An accountant is sometimes asked to probe into the history of a business, and to make a report on his findings. But, as his employers on such occasions are not concerned with knowledge for its own sake, he is usually told to restrict his researches straitly to recent years. So he has seldom the satisfaction of tracing the life of a firm from birth to death. Far more rarely has he the chance of studying a business which dates back to another age, whose methods are unlike anything that he has met before, and which even proves to have had some hand in the founding of a new empire and the shattering of an old one. Yet such has been my good fortune. Thomas and John Han- cock were merchants of Boston, Massachusetts, between 1724 and 1775. Thanks to the fame that John won as a patriot during the Revolution, a mass of the firm's accounts, letters, and papers have been preserved. I have tried to piece these documents together; The House of Hancock is my report. What is the good, I have been asked, of digging out the tale of a firm that has so long been dead and done with? The ques- tion is pertinent. A cynic might reply that the only real justi- fication for any historical research is that the researcher likes it. Even on these narrow grounds, The House of Hancock has been worth writing; but I venture to doubt the truth of the statement. To put the matter at its lowest, other people besides the researcher may find pleasure in learning about the past. Take my present subject: commerce during the Colonial era. In many minds - quite rightly - this trade is linked with smuggling, with privateers, with expeditions against the French, with the settlement of the frontier, and with other enterprises that have a certain tinge of romance. The books of our child- hood were filled with such matters. What could be more natural, when we reach adult years, than to wonder how these ad- ventures were organized? Who planned the smuggling trips? How were the privateers financed? By what means did General Wolfe's redcoats get their sparse rations of pickled pork and biscuits? The Hancocks were behind the scenes when all these things were being arranged; their account books reveal the mechanics of romance and empire. But I think that there are still other, and more serious, grounds for prying into old business records. Today a major branch of economics deals with the internal working of the business unit. Such learning is incomplete if it neglects the growth of administration in the past; and any generalized study of business history must have, as its basis, descriptions of individual firms like the Hancocks'. Nor is this all. Questions about the internal organization of business may be fare for specialists only; but many people are interested in the relations between business and society. How, for example, did rich families get their wealth? Did they per- form services to match their gains? Here is a set of questions that is often asked; and the story of the Hancocks gives the answer in one case (which may or may not be typical). Again, there is nowadays a widespread call for a planned economy and the state regulation of trade. The eighteenth century was also a period of planning and control; by looking at these things through the Hancocks' eyes, we can see blunders to be avoided. And similarly, where many other living issues are at stake, the historical approach is well suited to quicken our understanding. I do not suggest that a knowledge of business history will yield conclusive answers to present problems; abstract logic is usually the only valid basis on which these can be solved. To the imaginative person, however, study in the inviting field of history may well serve both as a lure to sterner mental tasks, and as a useful means for testing the soundness of his reasoning.
The house of Hancock: business in Boston 1724-1775